Development and optimization of an ammonia removal strategy for sustainable recycling of cell culture spent media in cultivated meat production: from concept to implementation - Pakbin, Babak; Amanipour, Armaghan; Amirvaresi, Arian; Shahsavari, Arash; Ovissipour, Reza (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAmmonia is a toxic metabolic waste produced during mammalian cell metabolism, with inhibitory effects against cell growth.MethodsThis study focuses on developing and optimizing an ammonia removal approach to support spent media recycling throughout sustainable cultivated meat biomanufacturing.ResultsAmong the various methods evaluated, the alkalization-stripping method was found to be significantly more efficient and rapid than other strategies to remove ammonia ions while preserving the remaining glucose contents. The optimized process parameters were determined to be a pH of 12 following a 15-minute stripping process, achieving more than 82% ammonia removal efficiency. When applied to lamb satellite cells, the treated spent media improved the cell growth rate without inducing any morphological changes.DiscussionA 50:50 ratio formulation of treated spent media to fresh media demonstrated an efficient, cost-effective, and environmentally friendly solution for spent media recycling, providing a practical approach to implementing sustainable media recycling in cultivated meat production.